A Book is a World unto Itself. On Writing the Novella The Glass Hill - Elísabet Jónsdóttir 1991- (2017)
The following thesis is the result of a Creative Writing Course taught by Anna Heiða Pálsdóttir at the English Department of the University of Iceland in the fall of 2016. It consists of an urban fantasy novella, The Glass Hill, and a report of the creative writing process. The novella is roughly 27000 words and the exposition is around 6800 words. The Glass Hill is set in the isolated and monster-infested kingdom of Pandion, where a powerful organization called the Royal Guard Institution has a choke-hold on the population and the government. The story tells the tale of a young governess named Gabriella Geoffrey, who is hired by an assassin named Poppy Morris to teach her son Emile. Soon it becomes apparent that the family Gabriella works for are not who they appear to be. Before she knows it, Gabriella has become a part of a conspiracy against the Royal Guard Institute’s rule, which puts her own life in danger. She is forced to confront her own past and how much damage the Royal Guard Institute is doing to her life and kingdom. The exposition contextualizes how the novella came into being. I discuss the inspiration for the novella, the laborious research I undertook into how to create a believable urban fantasy setting and the helpful advice I took from books on writing by professional authors. In addition, the exposition also details how the novella was written and then rewritten from scratch, how the plot was conceived and revised and the importance of themes and names as writing tools.